Abundancia y distribución de Aedes aegypti (Diptera: Culicidae) y dispersión del dengue en Guasave Sinaloa, México - García, Cipriano (Universidad de Costa Rica, 2011)
Abundance and distribution of Aedes aegypti (Diptera: Culicidae), and dengue dispersion in Guasave Sinaloa, México. Dengue is an important disease that affects humans, and is transmitted by A. aegypti. During 2006, a total of 477 cases of hemorrhagic dengue, and 1 510 of classic dengue were recorded in Sinaloa. Due to this high impact, a study on insect abundance and distribution, as well as their relationship with dengue dispersion, was carried out from April 2008 to March 2009 in Guasave, Sinaloa. The study included a total of six sectors in the city, considering 16 colonies; besides, 96 traps were distributed in these sectors to monitor the vector population density and female number per trap. The adult density index (ADI) and traps positive index (TPI) were calculated, and data were used to obtain the monthly dengue dispersion maps. The highest abundance of female (137 and 139) was found in July and August. In August and September the sectors 2, 4 and 6 showed the highest ADI values 2.44, 3.35 and 2.290, while TPI values were 56.25, 58.82 and 61.54, with the highest epidemiology dengue dispersion. The Pearson correlation (p < 0.05) showed better values with the precipitation (r=0.80) than mean temperature (r=0.76) with zero lag months; while the cases of classic dengue and hemorrhagic dengue (CD/HD) is mostly related with the precipitation (r=0.98), and minimum temperature (r=0.79), with two lag months. In conclusion, the ADI and TPI index, as well as the maps obtained, allowed us to know the location of epidemiologic dengue risk areas. This information can be used to develop better control measures biological and chemical for the mosquito, in this location.